Cultivating a Quality Culture through Total Quality Management: A Case Study of High School Excellence Programs in Yogyakarta - Pangestu, Fajar Agung; Yulianti, Feni; Oktarini, Shinta Lestari (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to analyze the implementation of Total Quality Management (TQM) in high schools, particularly in relation to the school's excellent programs that support educational quality. The focus of this study is how TQM principles are applied through these programs and their impact on school quality management in promoting student achievement.Method – This study uses a descriptive qualitative approach. It focuses on the phenomenon of implementation of TQM through the direct involvement of educational stakeholders, such as principals and teachers, as a crucial part of the data collection process. The study was conducted at Budi Mulia Dua International High School. This school was purposefully selected because it has implemented various excellent programs to improve the quality of education. Findings – This study found that TQM is implemented through four main programs: Student Advisory, University Preparation Program, Talent Optimizing Program, and BMD Award. The implementation of TQM through these excellent programs has produced measurable outcomes, including monthly student?advisory mentoring sessions, 41 students successfully entering national and international universities, 3 national level competition winners, and 10 academic award recipients. These four programs illustrate TQM principles such as continuous improvement, customer focus, and full involvement and contribute to the formation of a sustainable school quality culture. Research Implications – This research contributes principals and policy makers to design and refine excellent programs that instill TQM principles such as monthly student guidance to achieve improved achievement, continuing education and rewarding students to strengthen a sustainable quality culture.